Metabolomics-Based Identification of Metabolic Dysfunction in Frailty - Westbrook, Reyhan; Zhang, Cissy; Yang, Huanle; Tian, Jing; Guo, Shenghao; Xue, Qian-Li; Walston, Jeremy; Le, Anne; Abadir, Peter M (The journals of gerontology. Series A, Biological sciences and medical sciences, 2022)
Dysregulation of energy producing metabolic pathways has been observed in older adults with frailty. In this study, we used liquid chromatography-mass spectrometry technology to identify aging- and frailty-related differences in metabolites involved in glycolysis, the tricarboxylic (TCA) cycle, and other energy metabolism-related pathways in the serum of a cohort of community-dwelling adults aged 20-97 (n = 146). We also examined the relationship between serum levels of metabolites and functional measures, physical frailty, and risk status for adverse health outcomes. We observed elevated levels of TCA cycle and glycolytic intermediates in frail subjects; however, the differences in the levels of ATP and other energy metabolites between young, nonfrail, and frail adults were not significant. Instead, we found that serum levels of neurotransmitters N-acetyl-aspartyl-glutamate, glutamate, and γ-aminobutyric acid were significantly elevated in older adults with frailty. These elevations of glycolytic and TCA cycle intermediates, and neurotransmitters may be part of the biological signature of frailty.